The Protection of the Environment in Regional Human Rights Systems Outside Europe I: The Inter-American Human Rights System - Krajnyák, Enikő (Human Rights and Environmental Protection from a Central and Eastern European Perspective, 2026)
The Inter-American human rights system plays a crucial role in advancing the doctrine of environmental protection in human rights law, particularly by recognising the environmental rights in binding human rights instruments and allowing for their interpretation through the Inter-American Commission on Human Rights (IACHR) and the Inter-American Court of Human Rights (IACtHR). This chapter analyses the normative and jurisprudential framework for the protection of the environment in the Inter-American human rights system, and maps the current challenges of the interpretation of the right to a healthy environment.